KEDUDUKAN SAHABAT DAN ‘ADAALAHNYA - Darliana Sormin (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2016)
friend of Prophet Muhammad SAW is a person that has a relationship with him in believing of Islam till die. People can figure out about the friend of prophet MuhammadSAW through mutawatir, musyhur and mustafidh, self confession by equitable person.The experts of hadist believed that all friends of Prophet Muhammad SAW was fair enough, some arguments denied this yet. Mu’tazilah believed that Rasulullah’s friendis all fair besides in Shiffin and Jamal war. As a human being, a friend of Rasulullah also has some mistakes and defactiveness that is why the expert of hadist stated thatthey still need to test and make a research about them.